2010
DOI: 10.1038/ejcn.2010.79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changes in waist circumference on metabolic syndrome over a 6.6-year follow-up in Tehran

Abstract: Background/Objectives: This cohort study was conducted to evaluate the effect of waist change on metabolic syndrome (MetS) status and its parameters in 5720 participants, aged X20 years, of the Tehran Lipid and Glucose Study who were followed up for a mean of 6.6 years. Subjects/Methods: We measured waist circumference (WC) and MetS parameters at baseline (phase I: 1999) and at follow-up (phase III: 2008), and assessed this relationship across five groups: waist loss (oÀ2.0 cm); waist stable (À2.0 to 2.9 cm);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…ST-HIIT reduced WC in overweight/obese populations and LT-HIIT significantly improved WC and % body fat in overweight/obese populations. The average change in WC was 2.13 cm for ST-HIIT and 2.23 cm for LT-HIIT, both above the cut-off value of >2 cm WC decrease which is suggested to confer improvements in metabolic syndrome risk factors 98. These findings suggest that HIIT is an effective stimulus for reducing body fat levels (even in the absence of weight loss) for those individuals with large fat mass.…”
Section: Discussionmentioning
confidence: 76%
“…ST-HIIT reduced WC in overweight/obese populations and LT-HIIT significantly improved WC and % body fat in overweight/obese populations. The average change in WC was 2.13 cm for ST-HIIT and 2.23 cm for LT-HIIT, both above the cut-off value of >2 cm WC decrease which is suggested to confer improvements in metabolic syndrome risk factors 98. These findings suggest that HIIT is an effective stimulus for reducing body fat levels (even in the absence of weight loss) for those individuals with large fat mass.…”
Section: Discussionmentioning
confidence: 76%
“…Findings from a large meta‐regression analysis exploring WC as a predictor of CVD reported an increase of 1 cm in WC resulted in a 2% increase in CVD risk 84 . Using these findings in reverse and the fact that even modest reductions in WC (<2 cm) confer improvements in all metabolic risk factors, 86 it is evident from this NMA that COM‐LM exercise was most effective when it came to reducing WC and this is associated with a 5.5% decrease in CVD risk, followed by AE‐V and AE‐M with a 4.5% and 4% decrease, respectively. Furthermore, COM‐LM was more than twice as effective in changing CVD risk compared with either low or moderate load resistance training, a finding that both consistent with 87 and contradictory 16 to previously published meta‐analyses.…”
Section: Discussionmentioning
confidence: 99%
“… found a reduction only in an extended intervention (>12 weeks), with a decrease of ~2 cm. These reductions in waist circumference can be considered clinically relevant because even modest reductions (<2 cm) confer improvements in almost all risk factors present in metabolic syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Wewege et al (27) observed a significant effect of HIIT with a waist circumference reduction of~3 cm in adults with obesity, while Batacan et al (23) found a reduction only in an extended intervention (>12 weeks), with a decrease of~2 cm. These reductions in waist circumference can be considered clinically relevant because even modest reductions (<2 cm) confer improvements in almost all risk factors present in metabolic syndrome (76).…”
Section: Discussionmentioning
confidence: 99%